2016
DOI: 10.1111/appy.12252
|View full text |Cite
|
Sign up to set email alerts
|

Mental health status following severe sulfur mustard exposure: a long‐term study of Iranian war survivors

Abstract: The psychiatric morbidity in the chemically injured populations was remarkable and significantly different between the populations. The prevalence of mental illness in these groups highlights the need for the appropriate provision of mental health services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
(30 reference statements)
2
11
0
Order By: Relevance
“…The participants reported severe concerns regarding their general health, QOL and access to health care, which is consistent with previous studies. [16, 17, 22] All participants experienced deterioration in physical and mental health and wellbeing, and attributed their health problems to the CWA exposure, saying that the SM had become a “part of their body” and had damaged, and was continuing to damage, their organs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The participants reported severe concerns regarding their general health, QOL and access to health care, which is consistent with previous studies. [16, 17, 22] All participants experienced deterioration in physical and mental health and wellbeing, and attributed their health problems to the CWA exposure, saying that the SM had become a “part of their body” and had damaged, and was continuing to damage, their organs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the experience of CWAs and fear of renewed exposure to CWAs implies chronic poor health status and post-traumatic stress disorder (PTSD). [16, 22, 23] A recent study reports that SM effects on the respiratory system in particular are closely associated with psychiatric disorders. [22] A study on Iranian male war veterans revealed that SM victims with ophthalmological complications had lower health-related quality of life (HRQOL) compared to a control group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with the literature, reporting impairment in social abilities and a higher exposure to traumatic events as predictors of PTSD. (Ribeiro et al, ; Jakob, Lamp, Rauch, Smith, & Buchholz, ; Palgi, ; Idemudia et al, ; Gelkopf, Berger, Bleich, & Silver, ) Also, the exposure to toxic substances appears to be an important predictor of mental health disease, and especially of PTSD, (Khateri et al, ) due to the immediate physical harm and to the fear of long term medical disease (Pechura & Rall, ). Considering the WHODAS 2.0, higher scores in “understanding and communication,” suggesting the presence of impairment in social abilities, were predictors of higher scores in the PC‐PTSD and in the PCL‐5.…”
Section: Discussionmentioning
confidence: 99%
“…It also likely plays a role in the findings described in recent Iranian reports that have documented the persistent long-term and chronic effects of H exposure during the Iran-Iraq war that include ocular, dermatological, respiratory, gastrointestinal, haematological, neurological, neuromuscular, immunological and endocrine disruptions ( Fig. 3 ) [ [25] , [26] , [27] , [28] , [29] , [30] ].…”
Section: Introductionmentioning
confidence: 99%